Occupational therapists’ experiences of hegemony in a mental health setting: A practice-based enquiry - MaryBeth Gallagher; Nancy Bagatell (Scandinavian Journal of Occupational Therapy)
Background Despite valuing occupation, occupational therapists report barriers to enacting occupation-based practice. One barrier noted in the literature is hegemony, the dominance of one social group’s ideas over others. Specifically, biomedical and business models dominating healthcare are reported to significantly impact occupational therapists.Objective To describe how occupational therapists experience and manage hegemony in an acute mental health setting in the United States.Methods A community of practice scholars composed of nine occupational therapists participated in a practice-based enquiry. Scholars recorded their reflections on their practice and engaged in collective research discussions. All data were transcribed and analysed using narrative and thematic processes.Results Data analysis resulted in three themes that reflect the shifting and varying narratives of the community of practice scholars: (1) making waves; (2) staying afloat; and (3) sailing away.Conclusions and relevance The findings highlight the varied experiences and changing responses of the therapists as they gained awareness of hegemony in an acute mental health setting. While some therapists remained passive and ‘stayed afloat’ and others left the practice site or ‘sailed away’, others were empowered to ‘make waves’ and advocate for change and counter hegemony.